Pembelajaran Humanistik Dalam Pendidikan Agama Hindu Berbasis Lokal Genius - Temon Astawa, I Nyoman (PANGKAJA: JURNAL AGAMA HINDU, 2018)
Hinduism-based local genius education in humanistic learning in schools is an effort to implement values to achieve education with the nation's noble values. This local genius is very appropriate to be applied to Hindu religious education so it needs to be developed and re-socialized so that it can humanize humans. Many teachers or educators in less contextual learning rely solely on reading and memorizing, so there is saturation in learning. This article tries to discuss the form of learning that emphasizes on students themselves which are not just as objects, apply as subjects that deserve to be respected and aligned with their position. Hindu values, especially those based on local genius, display many humanist aspects that can be adopted by educators and then applied to students. The advantage gained from learning that is based on local genius in addition to education itself is also on the sustainability of the local genius. This integration presents a harmonious relationship between education and local culture. Between local culture and education no longer collide with each other so that the elimination between one of them can be avoided.